The Mainz Severity Score Index: a new instrument for quantifying the Anderson-Fabry disease phenotype, and the response of patients to enzyme replacement therapy - Whybra-Trümpler, Catharina; Kampmann, Christoph; Krummenauer, Frank; Ries, Markus; Mengel, Eugen; Miebach, Elke; Baehner, Frank; Kim, K.; Bajbouj, M.; Schwarting, Andreas; Gal, Andreas; Beck, Michael (Clinical genetics, 2004)
Anderson-Fabry disease (AFD) is an X-linked disorder caused by deficient activity of the lysosomal enzyme α-galactosidase A. The availability of enzyme replacement therapy (ERT) for this debilitating condition has led to the need for a convenient and sensitive instrument to monitor clinical effects in an individual patient. This study aimed to develop a scoring system - the Mainz Severity Score Index (MSSI) - to measure the severity of AFD and to monitor the clinical course of the disease in response to ERT. Thirty-nine patients (24 males and 15 females) with AFD were assessed using the MSSI immediately before and 1 year after commencing agalsidase alfa ERT. Control data were obtained from 23 patients in whom AFD was excluded. The MSSI of patients with AFD was significantly higher than that of patients with other severe debilitating diseases. The MSSI indicated that, although more men than women had symptoms classified as severe, overall, the median total severity scores were not significantly different between male and female patients. One year of ERT with agalsidase alfa led, in all patients, to a significant (p < 0.001) reduction in MSSI score (by a median of nine points). This study has shown that the MSSI score may be a useful, specific measure for objectively assessing the severity of AFD and for monitoring ERT-related treatment effects.
Gesehen am 16.05.2019